099 Aortic dilation in marfan syndrome: the use of a novel image post-processing technique. (December 2018) - Allen, G; Biffi, B; Milano, EG; Motensen, K; Couvreur, S; Capelli, C; Taylor, A; Schievano, S; Cervi, E
Abstract : Background: Marfan syndrome is a multi-systemic disorder characterized by progressive aortic dilation. Follow-up imaging is performed to monitor aortic dimensions, traditionally assessed by 2D diameter measurements, which cannot capture complex aortic shape variations. Statistical shape analysis is a novel technique that allows for a more comprehensive characterisation of the aortic morphology by analysing the overall 3D shape. Aims: The aim of the study was to create a 3D average (template) aorta for Marfan patients using statistical shape analysis and to study population shape variations that could be more indicative than traditional 2D measurements in patient follow-up. 3D reconstructions from cardiovascular magnetic resonance imaging of 46 Marfan patients were included in the study. Eleven shape components (shape modes) described the shape variations in the population and were compared with traditional morphometric and clinical data. Results: The first shape mode (mode 1) correlated with the vessel centreline length, thus representing mainly aortic size. Mode 1 dimensions increased with the increase of the aortic z-score derived from traditional image modalities. Good correlation was found between the aortic template and traditional dimensions. Conclusion: Prospective studies are required to assess the role of 3D aortic morphology in predicting clinical outcomes in this population.